1995
DOI: 10.1128/iai.63.12.4686-4694.1995
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis lipopolysaccharide is poorly recognized by molecular components of innate host defense in a mouse model of early inflammation

Abstract: Porphyromonas gingivalis is a gram-negative bacterium that is associated with periodontitis. It has been hypothesized that destruction of bone and periodontal connective tissue is associated with colonization of the subgingival crevicular space by P. gingivalis, although how these bacteria overcome innate host defenses is largely unknown. To examine the early cellular and molecular events of P. gingivalis interaction with host tissues, we compared lipopolysaccharide (LPS) isolated from this bacterium with Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 25 publications
(26 reference statements)
0
32
1
Order By: Relevance
“…In keeping with the proposed hypothesis of P. gingivalis stealth-like activities, its lipopolysaccharide is a poor inducer of inflammatory mediators in epithelial and endothelial cells and antagonizes their expression by lipopolysaccharide from other bacteria (28,36,191). However, and much like responses with P. gingivalis fimbriae, P. gingivalis lipopolysaccharide promotes the expression of proinflammatory cytokines and chemokines in monocytes ⁄ macrophages (265).…”
Section: Periodontopathogenic Modulation Of Cytokines ⁄ Chemokinesmentioning
confidence: 60%
“…In keeping with the proposed hypothesis of P. gingivalis stealth-like activities, its lipopolysaccharide is a poor inducer of inflammatory mediators in epithelial and endothelial cells and antagonizes their expression by lipopolysaccharide from other bacteria (28,36,191). However, and much like responses with P. gingivalis fimbriae, P. gingivalis lipopolysaccharide promotes the expression of proinflammatory cytokines and chemokines in monocytes ⁄ macrophages (265).…”
Section: Periodontopathogenic Modulation Of Cytokines ⁄ Chemokinesmentioning
confidence: 60%
“…Different organisms play different rô les in the disease process and P. gingivalis seems to be different from other gram-negative bacteria in its capacity to stimulate and activate the innate host inflammatory response (Darveau et al 1997). Recent studies showed that P. gingivalis plays an important rô le in suppressing the innate host inflammatory response by various mechanisms , Reife et al 1995, Cunningham et al 1996. P. gingivalis inhibits the ability of leukocytes to bind to endothelial cells and migrate into the extravascular compartment, and therefore blocks a key step in the inflammatory response (Darveau et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…P. gingivalis has been reported to have a biologically low reactive LPS. 41,42 The reason for this differential activation may be due to the difference in the structure of LPS molecules or the difference in their receptors on the cells. It has been shown that P. gingivalis-LPS extracted by the phenol-water method does not contain heptose and 2keto position of P. gingivalis-LPS differs from that of E. coli-LPS.…”
Section: Discussionmentioning
confidence: 99%